Exclusivity strategies for digital products across digital and physical markets - Rouven Seifert; Cord Otten; Michel Clement; Sönke Albers; Ole Kleinen (Journal of the Academy of Marketing Science, 2022)
Digital technologies allow versioning a product (e.g., a movie) for different physical and digital sequential distribution channels to target heterogeneous consumer segments, thereby creating exclusive offers. Extant literature on sequential distribution for movies largely concentrates on the theater-to-home-video window length (e.g., DVD), thus, neglecting digital distribution channels, particularly the potential of exclusive digital offers when multiple subsequent home video channels are available. We empirically examine the impact of exclusive digital movie offers on demand in digital and physical distribution channels. We fit a system of equations to a unique sample of 260 movies distributed in theaters, digital purchases, digital rentals, and physical purchases channels. Overall, the results indicate substantial profits from exclusive offers. Rather than sales cannibalizations, we find positive cross-channel demand spillovers from exclusive digital offers to delayed physical purchases. Exclusive home video offers outperform mere reductions in the theatrical exclusivity period; thus, implementing exclusive digital home video releases is a promising alternative to avoid conflict-prone reductions of the overall theater-to-home-video release window. Our findings are also relevant to industries that use different online and offline release windows (book publishers) or give exclusive access across different platforms (game publishers).
Keywords: 330; New product release timing; Digital marketing; Exclusive offerings; Channel order; Entertainment industry